2001
DOI: 10.1002/ptr.767
|View full text |Cite
|
Sign up to set email alerts
|

A reporter gene assay for the detection of phytoestrogens in traditional Chinese medicine

Abstract: Bupleurum & Peony Formula (Jia Wei Xiao Yao San) is a herbal formula which possesses a clinical history for the treatment of menopausal syndrome and menstrual irregularity. The present investigation reports the ability to monitor the formula's phytoestrogen content that will allow for the implementation of a standardization protocol that is based on a quantifiable biological response. Utilizing an oestrogen-sensitive chimeric receptor/reporter gene element which has been stably transfected into HeLa cells, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Therefore, much effort has gone into developing methods for the accurate quantification of phytoestrogens in plants, plant extracts, and botanicals, as well as in body tissues and fluids. The methods range from those that target specific compounds, such as high-performance liquid chromatography (HPLC) coupled to UV spectroscopy and/or mass spectrometry (17,96) and immunological methods such as enzyme-linked immunosorbent assay (19), to methods that do not chemically identify the active compound(s), such as in vitro estrogencity tests (the rodent uterotrophic assay) (47), microtitration assays with human ER (65), or analysis of ER binding using a reporter gene assay in yeast (134). Generally speaking, HPLC with UV detection is one of the simplest methods for determination of isoflavone phytoestrogen levels, both in plant extracts and animal tissues or body fluids (119,189).…”
Section: Dixonmentioning
confidence: 99%
“…Therefore, much effort has gone into developing methods for the accurate quantification of phytoestrogens in plants, plant extracts, and botanicals, as well as in body tissues and fluids. The methods range from those that target specific compounds, such as high-performance liquid chromatography (HPLC) coupled to UV spectroscopy and/or mass spectrometry (17,96) and immunological methods such as enzyme-linked immunosorbent assay (19), to methods that do not chemically identify the active compound(s), such as in vitro estrogencity tests (the rodent uterotrophic assay) (47), microtitration assays with human ER (65), or analysis of ER binding using a reporter gene assay in yeast (134). Generally speaking, HPLC with UV detection is one of the simplest methods for determination of isoflavone phytoestrogen levels, both in plant extracts and animal tissues or body fluids (119,189).…”
Section: Dixonmentioning
confidence: 99%
“…Crocin inhibits the cell growth of cancer cells [3,6,21]. Phytoestrogens are steroid-like plant compounds which may act as precursors to sex hormones [14]. In the present study, we indicated that the crude aqueous extracts from Chinese pangolin and wild pink are capable to promote the mammary gland development in immature mice although the constituents of both TCM effective in morphogenesis have remained undefined.…”
Section: Discussionmentioning
confidence: 62%
“…The elements of some TCM have been isolated from natural sources, such as glycyrrhizin from liquorice [4], crocin from crocus [3], phytoestrogens from Bupleurum and Peony Formula [14]. Glycyrrhizin has been reported to have antiviral activity against SARS-associated coronavirus [4].…”
Section: Discussionmentioning
confidence: 99%
“…When the effects of KSS/TSS on the serum levels of E 2 were examined, however, an increased serum E 2 concentration with a concurrently decreased FSH level was found in both of the 2 postmenopausal patients in our study. This may not be surprising, since a recent study [9] has shown that KSS contains a phytoestrogen. However, it is our impression that this fact has been overlooked in spite of the wide use of KSS.…”
Section: Discussionmentioning
confidence: 91%